ΑB‐Crystallin interacts and attenuates the tyrosine phosphatase activity of Shp2 in cardiomyocytes under mechanical stress. Issue 14 (23rd June 2016) - Gonçalves, Danieli C.; Marin, Talita M.; Pereira, Michelle B. M.; Santos, Aline M.; Paes Leme, Adriana F.; Franchini, Kleber G.
Abstract : The small heat shock protein αB‐Crystallin (CryAB, HspB5) and SH2 domain‐containing tyrosine phosphatase 2 (Shp2) are important molecules in heart response to pathophysiological stress. Here we show that CryAB interacts with and potentially regulates Shp2 catalytic activity in stretched cardiomyocytes. Such an interaction requires CryAB oligomer to attenuate Shp2 activation. Stretched cardiomyocytes show a robust CryAB/Shp2 association accompanied by a reduction in the Shp2 phosphatase activity. Accordingly, CryAB knock‐down in cardiomyocytes enhances Shp2 activity induced by mechanical stress. These results revealed a new role for CryAB, as a modulator of Shp2 phosphatase activity during a functionally relevant stimulus in cardiomyocytes. Abstract : CryAB directly binds SH2 domain‐containing tyrosine phosphatase (Shp2). Shp2 catalytic activity is reduced following binding to CryAB oligomer in vitro . CryAB potentially modulates Shp2 activity in cardiomyocytes under mechanical stress.